Autonomous Vehicles Technological Trends - Iclodean, Calin; Ovidiu Varga, Bogdan; Pfister, Felix (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The automotive industry has always been synonymous with research and innovation, but nowadays the industry is adding pressure and is establishing the agenda of the researchers from the field. Visions have been provided, and the hardware and the software exist; the only question remaining is: "who is going to deliver"? To answer this question, we encouraged scientists, researchers, industry specialists, and academics to share their vision of autonomous vehicles. What will the platform look like? What kind of hardware and software is most suitable? Who will make the connection between these two interdependent environments (and how), so that in the end the AI will define the process? These are the pressing issues of the current moment, and this Special Issue will help all those interested in the topic to promote their vision and ideas. Since the automotive field does not belong to a classical scientific field but has become an independent self-made scientific branch, all those who felt that they could contribute to this highly dynamic environment were requested to join in promoting their particular research or reviews in this Special Issue coordinated from both academia and the industry.